2015
DOI: 10.1038/jhh.2015.72
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma neopterin levels are associated with reduced endothelial function and arterial elasticity in hypertension

Abstract: Inflammation has been shown to play a pivotal role in the pathogenesis and development of hypertensive vascular injury. Neopterin is a novel marker of immune activation produced mainly by activated macrophages. Few data are available to show the association between neopterin and vascular function in hypertension. The present study was designed to investigate the relationship between neopterin levels related to arterial stiffness and endothelial function in patients with hypertension, and their changes after bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Previous studies have also shown that CRP is not correlated to FMD 30 . One study reported an inverse correlation between neopterin and FMD in hypertensives and a control group 31 , whereas another study found no correlation of FMD with neopterin in patients with coronary artery disease 32 . However, both these studies were small, including 54 and 30 participants, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that CRP is not correlated to FMD 30 . One study reported an inverse correlation between neopterin and FMD in hypertensives and a control group 31 , whereas another study found no correlation of FMD with neopterin in patients with coronary artery disease 32 . However, both these studies were small, including 54 and 30 participants, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, arterial stiffness and an increased carotid intima–media thickness are used as markers of subclinical atherosclerosis in hypertensive patients. 9 , 10 Unfortunately, no study has focused on the importance of EFT and the NLR in hypertensive patients. Thus, in the present study, EFT and the NLR were compared between hypertensive patients and a control group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that neopterin participates in the modulation of ROS‐mediated processes and activates the ROS‐sensitive transcription factor NF‐κB . In addition, neopterin is suggested to be linked to other pathological processes such as nitric oxide‐dependent apoptosis , fibrosis within the atria , and endothelial dysfunction , which may alter AF substrates and trigger AF.…”
Section: Discussionmentioning
confidence: 99%